Impact of Terms-of-Trade on Business Cycles of Slovakia, Czech Republic and Croatia - Karol Szomolányi; Martin Lukáčik; Adriana Lukáčiková (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Different theoretical and empirical studies lead to the different results. Different theories suggest a positive as well as a negative relation between the terms-of-trade and trade balance. The traditional Keynesian Harberger-Laursen-Metzler effect of the terms-of-trade on the trade balance is positive. According to the ObsfeldSvensson-Razin effect the positive relation between the terms-of-trade and trade balance is the smaller, the higher a persistence of the terms-of-trade shocks is. The empirical studies do not support statistically significant impact of the terms-of-trade on the output in the developing countries. The goal of the paper is to verify an impact of the terms-of-trade on the Slovak Czech and Croatian business cycles and trade balances. Using the structural vector auto-regression analysis of the terms-oftrade, trade balance, output, consumption and investment cyclical components, we show that the relationship between the terms-of-trade and trade-balance is negative in the Slovak and Czech economy. The relationship between the terms-oftrade and trade-balance is statistically insignificant in the Croatian economy. Termsof-trade shocks explain only small fraction of business cycles in the Slovak, Czech and Croatian economies. Data exhibit Obstfeld-Svensson-Razin effect of the termsof-trade on the trade balance.
Keywords: C32; E32; F14; 330; innovation; terms-of-trade; business cycle; Slovak economy; Czech economy; Croatian economy; trade balance; market